Erratum to: Production of biosurfactants by soil fungi isolated from the Amazon forest (International Journal of Microbiology (2018) 2018 (5684261) DOI: 10.1155/2018/5684261) - Sena, Hellen Holanda (2018)
This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. In the article titled "Production of Biosurfactants by Soil Fungi Isolated from the Amazon Forest" [1], the Acknowledgements section was missing from the published article due to a production error and should be added as follows. © 2018 Hellen Holanda Sena et al.